Serum VEGF levels in infants at risk for developing retinopathy of prematurity (Ukrainian Journal of Ophthalmology, 2025)
Background: Because excessive growth of abnormal retinal vessels in the developing eye of the premature infant underlies retinopathy of prematurity (ROP), it may be hypothesized that a change in vascular endothelial growth factor (VEGF) level in the infant’s vascular bed predicts the course of the disease.Purpose: To determine serum VEGF levels and to assess changes in these levels over time in infants at risk for developing ROP.Materials and Methods: Twenty three infants born preterm underwent examinations for ROP. Two examinations were performed 14±3 days apart. A 1-ml blood sample was collected to obtain a 0.5-ml serum sample from each infant. Serum was frozen at -20° С until analysis. Serum VEGF levels were assessed by enzyme-linked immunosorbent assay (ELISA) method using Human VEGF-A ELISA Kit (Ray Biotech Inc., Norcross, GA) following the manufacturer’s instructions. Newborns were divided into two groups: those who exhibited ROP progression or absence of improvement (Group 1), and those who exhibited regression of ROP (Group 2). A Student’s t-test or Wilcoxon rank-sum test was used for two-group comparison.Results: There were no significant differences between groups with regard to birth weight or gestational age (p
Keywords: retinopathy of prematurity; VEGF